Budaya Penghakiman Digital dalam Perspektif Etika Kristen: Studi Tentang Cancel Culture dan Cyberbullying - Krisnawati Harefa; Ferdinand Sitinjak (International Forum of Researchers and Lecturers, 2026)
The development of social media has significantly changed human communication patterns. On the one hand, digital media provides a space for freedom of expression, but on the other hand, it has also given rise to digital judgmental cultural phenomena such as Cancel culture and cyberbullying. These phenomena often give rise to verbal violence, public humiliation, and massive social exclusion in cyberspace. This article aims to analyze the phenomena of Cancel culture and cyberbullying from a Christian ethical perspective. The research method used is a literature review with a theological-ethical approach. The results of the study indicate that the digital judgmental culture contradicts the principles of love, respect for human dignity as the Imago Dei, and Christian communication ethics taught in the Bible. Christian ethics views every individual as having value before God, so the practices of humiliation, digital bullying, and public judgment are unjustifiable. The church and believers are called to present constructive, loving, communication in the digital space.